Long-term outcome analysis of reduced-intensity allogeneic stem cell transplantation in patients with mantle cell lymphoma: a retrospective study from the EBMT Lymphoma Working Party - Robinson, Stephen; Dietrich, Sascha; Dreger, Peter (Bone marrow transplantation, 2018)
Reduced-intensity allogeneic stem cell transplantation (RIST) is usually reserved for patients with mantle cell lymphoma who relapse after an autoSCT. However, the long-term efficacy of RIST and its curative potential have not been clearly demonstrated. We studied the long-term outcome of patients receiving a RIST for MCL as reported to the EBMT. A total of 324 patients, median age 57 years (range 31-70), underwent a RIST between 2000 and 2008; 43% of the patients had received >3 lines of prior therapy, including an autoSCT in 46%. Non-relapse mortality (NRM) was 10% at 100 days and 24% at 1 year and was lower for patients receiving anti-thymocyte globulin (ATG)/ALG (RR 0.59, p = 0.046). After a median follow-up of 72 months (range 3-159), 118 patients relapsed at a median of 8 months post RIST (range 1-117). The cumulative incidence of relapse was 25% and 40% at 1 and 5 years, respectively, and was associated with chemorefractory disease (HR 0.49, p = 0.01) and the use of CAMPATH (HR 2.59, p = 0.0002). The 4-year progression-free survival rate and overall survival rate was 31 and 40%, respectively. RIST results in long-term disease-free survival in about 30% of the patients, including those patients relapsing after a prior autoSCT.
Gesehen am 14.04.2020